Short- and Long-Term Effectiveness of a Subject’s Specific Novel Brain and Vestibular Rehabilitation Treatment Modality in Combat Veterans Suffering from PTSD - Carrick, Frederick Robert; Pagnacco, Guido; McLellan, Kate; Solis, Ross; Shores, Jacob; Fredieu, Andre; Brock, Joel Brandon; Randall, Cagan; Wright, Cameron; Oggero, Elena (Frontiers in Public Health, 2015)
Abstract Introduction: Treatment for post-traumatic stress disorder (PTSD) in combat veterans that have a long-term positive clinical effect has the potential to modify the treatment of PTSD. This outcome may result in changed and saved lives of our service personnel and their families. In a previous before-after-intervention study we demonstrated high statistical and substantively significant short-term changes in the Clinician Administered DSM-IV PTSD Scale (CAPS) scores after a two week trial of a subject's particular novel brain and vestibular rehabilitation (VR) program. The long-term maintenance of PTSD severity reduction was the subject of this study. Material and Methods: We studied the short and long term effectiveness of a subject's particular novel brain and VR treatment of PTSD in subjects who had suffered combat-related traumatic brain injuries in terms of PTSD symptom reduction. The trial was registered as ClinicalTrials.gov Identifier: NCT02003352. We analyzed the difference in the CAPS scores pre and post treatment (one week and three months) using our subjects as their matched controls. Results: The generalized least squares (GLS) technique demonstrated that with our 26 subjects in the 3 timed groups the R2 within groups was 0.000, R2 between groups was 0.000 and overall the R2 was 0.000. The GLS regression was strongly statistically significant z = 21.29, p < 0.001, 95% CI [58.7, 70.63]. The linear predictive margins over time demonstrated strong statistical and substantive significance of decreasing PTSD severity scores for all timed CAPS tests. Discussion: Our investigation has the promise of the development of superior outcomes of treatments in this area that will benefit a global society. The length of the treatment intervention involved (two weeks) is less that other currently available treatments and has profound implications for cost, duration of disability and outcomes in the treatment of PTSD in combat veterans.